Do I care if you are paid? A field experiment on charitable donations - Uri Gneezy; Holger Rau; Anya Samek; Lilia Zhurakhovska (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This study investigates how information on solicitors' compensation affects charitable giving in a door-to-door field experiment with more than 2,800 households. We vary whether solicitors are paid or not and the information about this compensation that potential donors receive. Relative to the treatment in which potential donors are not informed about the solicitor's compensation, donations increase by 16% when potential donors are informed that solicitors are paid, but are not effected when donors are informed that solicitors are unpaid. The effect is driven by female donors, who increase their donations by 88%. Our findings suggest that if charities pay their solicitors, it could be beneficial to communicate this information to donors.
Keywords: 330; charitable giving; field experiment; information